Population ageing, intergenerational transfers and demographic dividend in Ecuador - Rosero Bixby, Luis (2015)
This paper analyses economic flows over the lifecycle in Ecuador, a middle-income country that is anticipating rapid population ageing. Using the National Transfer Accounts (NTA) framework, the paper develops estimates of age patterns of production and consumption, as well as the magnitudes of the various types of economic transfers between age groups for Ecuador for 2006 and 2011. These estimates add to the database of countries participating in the international collaborative NTA project. Analyses of the estimates point to important socioeconomic transformations that took place in Ecuador between 2006 and 2011, such as increases in public transfers to older persons and in older persons’ net transfers to younger people. The paper concludes with an assessment of the demographic dividend in Ecuador, noting that the window of accelerated economic growth associated with the favourable demographic shifts that led to an increase in the ratio of producers to consumers would soon close.